Bão từ và bão điện ly ngày 6-7/4/2000 và ngày 31/3/2001 quan sát được tại Phú Thụy - Minh, Lê Huy; Lan, Trần Thị; Hồng, Phạm Thị Thu (Vietnam Journal of Earth Sciences, 2004)
Geomagnetic and ionospheric storms on the 6-7th Avril 2000 and on the 31st March 2001 observed at Phu Thuy